La protección jurídica ambiental del agua para consumo humano. Panorama de dos provincias argentinas y del ámbito internacional. (2016)
The objective of this article is to analyze the level of evolution of environmental legal protection of water for human consumption in the regulations of the provinces of Buenos Aires and Santa Fe (Argentina) and in the international sphere, through the application of three of the development paradigms worked out by Michael Colby: a) environmental protection, b) resource management and c) eco development. The methodology used is qualitative, fundamentally legal hermeneutics. We can conclude that both provincial legal systems have a strong anthropocentric approach, privileging the interests of man over the rights of nature/environment, and do not delve into essential aspects such as social, environmental and cultural.